A brief review of Odonata in mid-Cretaceous Burmese amber. Issue 1 (2nd January 2020) - Zheng, Daran; Jarzembowski, Edmund A.
Abstract : Odonatans are rare as amber inclusions, but quite diverse in Cretaceous Burmese amber. In the past two years, over 20 new species have been found by the present authors after studying over 250 odonatans from 300, 000 amber inclusions. Most of them have now been published, and here we provide a brief review. Three suborders of crown Odonata have been recorded, including the damselfly families or superfamilies Platycnemididae, Platystictidae, Perilestidae, Hemiphlebiidae, Coenagrionoidea, Pseudostigmatoidea, Mesomegaloprepidae and Dysagrionidae, plus the dragonfly families Lindeniidae, Gomphaeschnidae and Burmaeshnidae, and the damsel-dragonfly family Burmaphlebiidae.